Lithium-Induced Treatment-Resistant Akathisia: A Case Report and Literature Overview. Issue 3 (May 2021) - Demir, Bahadir; Sancaktar, Muhammet; Altindag, Abdurrahman
Abstract : Objective: A case of lithium-induced akathisia is presented, a side effect that has only rarely been reported in the literature. Case: A 49-year-old married woman was hospitalized 4 weeks before her presentation to our outpatient clinic due to a manic episode with psychotic features. Lithium carbonate (600 mg/d) was started for mood stabilization and soon, thereafter, she developed akathisia, which did not respond to reducing the dose of risperidone and addition of propranolol and lorazepam. The akathisia resolved when lithium was discontinued and replaced with valproic acid for mood stabilization. Discussion: Akathisia is commonly overlooked or misdiagnosed by physicians. This case report is presented to alert physicians to the possible emergence of akathisia when the lithium ion is prescribed for mood stabilization.